European Experience in Adapting Social and Economic Development to Crisis Situation: Programs and Financial Instruments - Kornіvska Valerіa O. (PH "INZHEK", 2021)
The paper presents analysis of European counter-crisis response programs: investment initiatives in response to the coronavirus; REACT-EU package of measures; a long-term recovery program (budget for 2021-2027) and Next Generation EU; and a banking package of measures titled “Supporting businesses and households amid COVID-19”. The sources of financial instruments for the recovery and adaptation of EU member states to the transcrisis state are described, and the most effective mechanisms for supporting entrepreneurship in the COVID-19 crisis are shown. The example of Slovakia and Poland is used to demonstrate the European experience in organizing the credit process, providing guarantees, intensifying social entrepreneurship in the face of the ongoing epidemic shock. The European investment trends and the participation of financial intermediaries in the post-crisis recovery are determined and used as a basis to characterize nationalization of the European long-term investment process. The special role of the state and the formation of state funds in the process of ensuring the effective adaptation of the Ukrainian financial and institutional environment to new challenges is substantiated; the importance of developing long-term programs for adapting the Ukrainian economy and society to the challenges of sanitary, humanitarian, climatic and political and economic nature, as well as forming appropriate institutions is shown. It is concluded that, given the peculiarities of the operational behavior of Ukrainian banking institutions, which are now focused on operations with government securities and commission activities, the adaptation investment process should be provided by public financial institutions.